Nano-Scale Secondary Ion Mass Spectrometry: A Paradigm Shift in Soil Science - Mir, Yasir Hanif; Qin, Anzhen; Mir, Shakeel; Rahman, Shafeeq Ur; Mushtaq, Mehnaza; Ganie, Mumtaz A.; Chesti, M. H.; Bhat, Javid A.; Baba, Zahoor A.; Bhat, M. Auyoub; Khan, Inayat M.; Rasool, Rehana; et al. (Journal of Spectroscopy, 2024)
Soils exhibit structural heterogeneity across diverse spatio-temporal scales, yielding myriad of microhabitats, highlighting the need for a nuanced understanding of the intricate interactions within the soil matrix. At the nanometer scale, the interplay among organic matter (OM), mineral particles, and microbiota intricately govern the long-term destiny of soil carbon (C), nutrient cycling, and the fate of both organic and inorganic pollutants. Notably, the sorption of soil organic matter (SOM) onto smaller clay particles and its entrapment in microaggregates further contribute to this complex dynamic. Understanding these processes depends on recognizing their scale-dependent nature, necessitating sophisticated techniques for investigation. Although various methods are employed across scales, the current set of techniques still lacks the requisite sensitivity and resolution for microscale data collection. To address this limitation, the adoption of novel microscopic and spectroscopic techniques capable of probing molecular, isotopic, and elemental patterns at the micro to nano scale becomes imperative. Among these cutting-edge methodologies, the nano-scale secondary ion mass spectrometer (NanoSIMS) emerges as a paradigm-shifting tool. Representing the latest evolution in ion microprobes, NanoSIMS seamlessly integrates high-resolution microscopy and isotopic analysis, maintaining unparalleled signal transmission and spatial resolution, reaching as fine as 50 nm. Its capabilities extend beyond conventional applications in science, as evidenced by recent breakthroughs in utilizing NanoSIMS to study biophysical interfaces in soils. This article underscores the pressing need to advance the incorporation of NanoSIMS as a pioneering instrumentation technique in soil studies. Furthering the implementation of this novel instrumentation technique in soil studies will pave avenues and aid in the advancement of future research.